A Narrative Review on the Update in the Prevalence of Infantile Colic, Regurgitation, and Constipation in Young Children: Implications of the ROME IV Criteria - Muhardi, Leilani; Aw, Marion M.; Hasosah, Mohammed; Ng, Ruey Terng; Chong, Sze Yee; Hegar, Badriul; Toro-Monjaraz, Erick; Darma, Andy; Cetinkaya, Merih; Chow, Chung Mo; Kudla, Urszula; Vandenplas, Yvan (Frontiers in Pediatrics, 2022)
Regurgitation, colic, and constipation are frequently reported Functional Gastrointestinal Disorders (FGIDs) in the first few years of life. In 2016, the diagnostic criteria for FGIDs were changed from ROME III to ROME IV. This review assesses the prevalence of the most frequent FGIDs (colic, regurgitation and constipation) among children aged 0-5 years after the introduction of the later criteria. Articles published from January 1, 2016 to May 1, 2021 were retrieved from PubMed and Google Scholar using relevant keywords. A total of 12 articles were further analyzed based on the inclusion and exclusion criteria. This review consists of two studies (17%) from the Middle East, three (25%) from Asia, two (17%) from the USA, three (25%) from Europe, and one (7%) from Africa. Three studies (25%) were based on data obtained from healthcare professionals, while the rest were parent or caregiver reports. About half of the retrieved studies used the ROME IV criteria. Among infants aged 0-6 months, the reported prevalence of colic ranged between 10%-15%, whilst that of regurgitation was 33.9%, and constipation was 1.5%. Among infants aged 0-12 months, the reported prevalence of regurgitation and constipation were 3.4%-25.9% and 1.3%-17.7%, respectively. The reported prevalence of constipation was 1.3%-26% among children aged 13-48 months and 13% among children aged 4-18 years. Despite the large variations due to differences in diagnostic criteria, study respondents and age group, the prevalence of infantile colic was higher, while that for infantile regurgitation and constipation were similar using the ROME IV or III criteria.